2019
DOI: 10.4038/besl.v13i1.7664
|View full text |Cite
|
Sign up to set email alerts
|

Colour associated thermal impacts: manifestation and contributing factors with reference to red and blue

Abstract: Theory of colour -a long-established tradition of artists -differentiates between the impacts of warm and cool colours respectfully on human beings. The lack of scientific and statistically substantiated knowledge on aforesaid colour associated thermal perception (CTP) deems to hinder its optimum integration in creating responsive built environments. This investigation seeks scientific explanation on manifestation and contributing factors of CTP with reference to a warm colour (red-RTP) and a cool colour (blue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…As cited in Mahnke (1996), Scheurle (1971) reported that most test subjects perceived a red room to be significantly warmer than a blue counterpart, although temperature settings were the same for both. Hettiarachchi (2014) researched on the logic behind manifestation of colour associated thermal perception with reference to red and blue colours in a controlled laboratory environment (26 o C/ 50% rh /350 lux) testing three hypothetical sub questions; the possibility of thermal perception triggered by colour stimuli to be an actual thermal sensation, a biological response (alteration in core body temperature) or a psychological response. The psychological parameters were statistically significant against the parameters of actual thermal sensation and core body temperature and thus, the study statistically established the fact that thermal perception associated with colour is a psychological response.…”
Section: Supportive Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…As cited in Mahnke (1996), Scheurle (1971) reported that most test subjects perceived a red room to be significantly warmer than a blue counterpart, although temperature settings were the same for both. Hettiarachchi (2014) researched on the logic behind manifestation of colour associated thermal perception with reference to red and blue colours in a controlled laboratory environment (26 o C/ 50% rh /350 lux) testing three hypothetical sub questions; the possibility of thermal perception triggered by colour stimuli to be an actual thermal sensation, a biological response (alteration in core body temperature) or a psychological response. The psychological parameters were statistically significant against the parameters of actual thermal sensation and core body temperature and thus, the study statistically established the fact that thermal perception associated with colour is a psychological response.…”
Section: Supportive Literaturementioning
confidence: 99%
“…One study by Hettiarachchi (2014) recommended the integration of colour to psychologically manipulate the perceived thermal environment; against actual thermal condition to alter the comfort zone. As a follow-up research, the current investigation attempts to fill the aforementioned research gaps simultaneously by developing the usage of applied colour to psychologically manipulate the perceived thermal condition against the actual thermal condition; as an effective and affordable hybrid method of conserving energy spent on ceiling fans in industrial buildings.…”
Section: Research Gapmentioning
confidence: 99%